The Effect of Technology Adoption and Service Quality on Patient Satisfaction (Case Study on Digital Dentistry Adoption at Densthetica Clinic West Sumatra) - Fadlan, Muhammad; Lahindah, Laura (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of digital dentistry service adoption and service quality on patient satisfaction at Densthetica Clinic West Sumatra. With the development of technology, the application of digital services in the field of dentistry is becoming increasingly important to improve efficiency and service quality. This study uses a quantitative method with a survey approach to collect data from Densthetica Clinic patients. The questionnaire used consisted of questions regarding the adoption of digital dentistry services, service quality, and patient satisfaction. The results showed that the adoption of digital dentistry services and service quality had a significant effect on patient satisfaction. From the multiple linear regression analysis, it is known that both independent variables contribute positively to patient satisfaction, with service quality having a more dominant influence.